BoneJ: Free and extensible bone image analysis in ImageJ - Doube, Michael; Klosowski, Michal M.; Arganda-Carreras, Ignacio; Cordelieres, Fabrice P.; Dougherty, Robert P.; Jackson, Jonathan S.; Schmid, Benjamin; Hutchinson, John R.; Shefelbine, Sandra J. (Bone, 2010)
Bone geometry is commonly measured on computed tomographic (CT) and X-ray microtomographic (μCT) images. We obtained hundreds of CT, μCT and synchrotron μCT images of bones from diverse species that needed to be analysed remote from scanning hardware, but found that available software solutions were expensive, inflexible or methodologically opaque. We implemented standard bone measurements in a novel ImageJ plugin, BoneJ, with which we analysed trabecular bone, whole bones and osteocyte lacunae. BoneJ is open source and free for anyone to download, use, modify and distribute. © 2010 Elsevier Inc.
Created from Fastlane, Scopus look-up
Keywords: Bone; Image; Morphometry; Open source; Software; Tomography